Generation of a novel mouse model for the inducible depletion of macrophages in vivo. Issue 1 (20th September 2012) - Gheryani, Nabeia; Coffelt, Seth B.; Gartland, Alison; Rumney, Robin M.H.; Kiss‐Toth, Endre; Lewis, Claire E.; Tozer, Gillian M.; Greaves, David R.; Dear, T. Neil; Miller, Gaynor
Abstract Macrophages play an essential role in tissue homeostasis, innate immunity, inflammation, and wound repair. Macrophages are also essential during development, severely limiting the use of mouse models in which these cells have been constitutively deleted. Consequently, we have developed a transgenic model of inducible macrophage depletion in which macrophage‐specific induction of the cytotoxic diphtheria toxin A chain (DTA) is achieved by administration of doxycycline. Induction of the DTA protein in transgenic animals resulted in a significant 50% reduction in CD68+ macrophages of the liver, spleen, and bone over a period of 6 weeks. Pertinently, the macrophages remaining after doxycycline treatment were substantially smaller and are functionally impaired as shown by reduced inflammatory cytokine production in response to lipopolysaccharide. This inducible model of macrophage depletion can now be utilized to determine the role of macrophages in both development and animal models of chronic inflammatory diseases. genesis 51:41‐49, 2013. © 2012 Wiley Periodicals, Inc.